Export of educational services as a factor in the development of the global education market in modern conditions - D. O. Munich (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. For successful export of educational services, the supplier countries develop marketing strategies, tune the courses in line with the requirements of international standards, provide support in the form of visa services, accommodation and integration into the local community. Goal. The purpose of the research is to reveal the role and influence of educational export as a factor of development of the global market of educational services in modern conditions. Materials and methods. The study is based on the analysis of the role of export of educational services in the global market. Results and discussion. The article analyses how the export of education affects the development of the educational market in modern conditions and what trends can be anticipated in the future. The level of export potential of leading countries and their influence on the world economy is determined. The article presents the factors influencing the growth of exports of educational services, the rating of the global market share of international mobile students in the following areas: medicine, engineering, business and management and other leading areas of study. It also studies the platforms of leading countries for active training of foreign students, strategies for the development of education exports in Russia and measures necessary for the successful realization of the export potential of Russian education. The scientific novelty of the article consists in the study of the relationship between the export of educational services and improving the quality of education, the impact of innovative technologies and online platforms on the export of education and the global education market as a whole. Conclusion. As a result, the factors influencing the growth of export of educational services in the context of global market development and indicators of efficiency of digitalisation of education abroad are identified and characterized.